Blindspot. the complete third season [videorecording (DVD)] - Gero, Martin, 1977- (Blindspot, 2018)
In the third season, Weller finally tracks down Jane, who's been on the run. After the two discover her new hidden tattoos, Jane is forced to return to the FBI, where Weller, Jane, and the rest of the team set out to solve these new puzzles and stop the dangerous conspiracies they reveal.